Impact of Diabetes Mellitus on Hospitalization for Heart Failure, Cardiovascular Events, and Death. Issue 10 (8th September 2015) - Cavender, Matthew A.; Steg, Ph. Gabriel; Smith, Sidney C.; Eagle, Kim; Ohman, E. Magnus; Goto, Shinya; Kuder, Julia; Im, Kyungah; Wilson, Peter W.F.; Bhatt, Deepak L.
<x xml:space="preserve">Abstract</x> Background— Despite the known association of diabetes mellitus with cardiovascular events, there are few contemporary data on the long-term outcomes from international cohorts of patients with diabetes mellitus. We sought to describe cardiovascular outcomes at 4 years and to identify predictors of these events in patients with diabetes mellitus. Methods and Results— The Reduction of Atherothrombosis for Continued Health (REACH) registry is an international registry of patients at high risk of atherothrombosis or established atherothrombosis. Four-year event rates in patients with diabetes mellitus were determined with the corrected group prognosis method. Of the 45 227 patients in the REACH registry who had follow-up at 4 years, 43.6% (n=19 699) had diabetes mellitus at baseline. The overall risk and hazard ratio (HR) of cardiovascular death, nonfatal myocardial infarction, or nonfatal stroke were greater in patients with diabetes compared with patients without diabetes (16.5% versus 13.1%; adjusted HR, 1.27; 95% confidence interval [CI] 1.19–1.35). There was also an increase in both cardiovascular death (8.9% versus 6.0%; adjusted HR, 1.38; 95% CI, 1.26–1.52) and overall death (14.3% versus 9.9%; adjusted HR, 1.40; 95% CI, 1.30–1.51). Diabetes mellitus was associated with a 33% greater risk of hospitalization for heart failure (9.4% versus 5.9%; adjusted odds ratio, 1.33; 95% CI, 1.18–1.50). In patients with diabetes mellitus, heart failure at baseline was independently associated with cardiovascular death (adjusted HR, 2.45; 95% CI, 2.17–2.77; P<0.001) and hospitalization for heart failure (adjusted odds ratio, 4.72; 95% CI, 4.22–5.29; P<0.001). Conclusions— Diabetes mellitus substantially increases the risk of death, ischemic events, and heart failure. Patients with both diabetes mellitus and heart failure are at particularly elevated risk of cardiovascular death, highlighting the need for additional therapies in this high-risk population.